Pengaruh Rasio Keuangan Terhadap Kinerja Keuangan Perusahaan Perbankan - Ni Putu Shinta Larassati Dewi; I Gusti Ngurah Sanjaya; Luh Kade Datrini (Jurnal Riset Akuntansi Warmadewa, 2026)
The companys success can be seen from the company's funding conditions which are measured using ratio analysis. The aim of the research is to analyze the relationship between liquidity ratios, solvency, activity and the financial performance of banking company listed on the IDX in 2021-2023. Data was collected using non-participant observation methods. The sample obtained through purposive sampling with 38 sample units and 84 observations. Data was obtained through non-participant observation methods with panel data regression analysis. The test results show that financial performance is influenced by the solvency ratio, while liquidity and activity have no influence on financial performance.